Hans Kelsen’s thoughts about the law and its relevance to current legal developments - Hadi, Syofyan; Michael, Tomy (Technium Social Sciences Journal, 2022)
The purpose of this study is to describe and explain Hans Kelsen’s ideas on law and analyze its relevance to current legal developments. This research is a normative legal research with a statutory and conceptual approach. The results of the study found that there are 2 (two) main ideas or theories about law that proposed by Hans Kelsen, namely (1) pure legal theory that views "what the law is" or "law as such", therefore the law must be separated from morality, justice, and others; and (2) the theory of hierarchy of norms which views that legal norms in the state have a hierarchy or level (the higher norms and the lower norms).. Pure legal theory has no relevance to current legal developments, because currently judges are tasked with enforcing law and justice and are required to explore the values ​​and sense of community justice in making decisions. The government is also given the authority to act based on discretionary authority. Theory of hierarchy of norms still has relevance to current legal developments because currently a judicial review mechanism is used on legal norms to maintain their validity.